THE ROLE OF PHILATELY IN MUSICAL EDUCATION AND CROSS-CULTURAL INTERACTION - Makris, Ioannis (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
In our increasingly diverse societies, it is essential to ensure harmonious interaction among peoples and groups with plural, varied, and dynamic cultural identities as well as a willingness to co-exist. Therefore, the fostering of dialogue among cultures and peoples can only occur on the basis of the recognition of and respect for cultural diversity. In this context, for the dialogue and the interaction across the cultures, educators need to create educational actions and strategies so that cross-cultural dialogue and interaction may take place. Philately and music are two tools that can help teachers in that direction. Philately is the study of stamps, postal history, and other related items. Philately is an incredible journey into the world of stamps which give a unique view of the history and culture of a country. Stamp collections entail a wide range of topics. In this paper, we considered it useful to confine to thematics related to music, musical instruments, great musicians, etc. The present study aims at showing how specific stamp thematics can be used as a means towards teaching music and, in particular, history of music; musical instruments; and ethnomusicology. It also aims at highlighting how students, through observation and research, can discover information about other cultures and nations by taking up a creative and affordable hobby that is both educational and fun. Last, the present research focuses on how philately and stamp collections related to music can become an effective educational tool for teachers and the educational system towards promoting cross-cultural dialogue and interaction.